Formulation of Recipes and Organoleptic Properties of Tinuktuk as Simalungun Traditional Food - Tarigan, Novriani; Silalahi, Jansen; Sihotang, Urbanus (Syntax Corporation Indonesia, 2024)
Tinuktuk is a traditional spice sauce of the simalungun ethnic group. It is believed as a traditional health icon To search the best formulation of ingredients', to search the best production process and to evaluate its organoleptics properties. The search for formulation ingredients is an exploratory qualitative study with participant observation method. The organoleptic test was carried out by fifty untrained panelists on a scale of 1 (dislike) to 5 (very like). Organoleptic values ​​including taste, aroma, texture and color Six formulations of tinuktuk, containing of 8 to 15 ingredients. Three kinds of production process: first by mashing the fresh ingredients and then roasting them. The second process is mashing the rosated material. The third is a combination of both processes. These processes could be distingueished by the organoleptic values. The incremented values resulted from T5, T1, T3 formulations. T3 formula contains 15 ingredients use the third production process. This value could be taken as a reference for tinuktuk standard.